2021
DOI: 10.1016/j.adro.2020.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Single Institution Experience of Postoperative Electron Beam Radiation Therapy in the Treatment of Keloids

Abstract: Purpose Surgical excision followed by postoperative radiation therapy is an accepted modality to prevent keloid recurrence. Our practice has been to use electron beam radiation postoperatively to prevent recurrence, and we share our experience with this method in this study. Methods and Materials Twenty-two patients with 40 keloids treated postoperatively with electron beam radiation at our institution from 2014 to 2019 were analyzed retrospectively. Electron beam radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…19 Many studies have found no difference in the ease of use, the side effects such as hyperemia or pigment changes, or the rates of recurrence between HDR brachytherapy and External beam therapy. [20][21][22] We have used both modalities as were available and suitable for each case. All the children in this study were given electron beam radiotherapy and they tolerated it well without panicking or fidgeting, maybe because it is painless.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many studies have found no difference in the ease of use, the side effects such as hyperemia or pigment changes, or the rates of recurrence between HDR brachytherapy and External beam therapy. [20][21][22] We have used both modalities as were available and suitable for each case. All the children in this study were given electron beam radiotherapy and they tolerated it well without panicking or fidgeting, maybe because it is painless.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative RT has been proven to be the most effective treatment compared with other local treatments, and recurrence rates have been reported to vary from less than 10% to 20% or more. 3,[12][13][14] There is a continued lack of consensus among physicians regarding the dose protocols in keloid treatment. 1,15,16 Furthermore, owing to the location propensity of these keloids, the recurrence rate may differ depending on the keloid's location, and the proportion of the sites in the previous studies may have also contributed to the overall recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…16 While surgical excision followed by RT is widely accepted as an effective modality to treat keloids, optimum fractionation schedule is still elusive. Doses have ranged from prolonged schedules of 20 Gy in five fractions 19,20 to upcoming single-fraction schedules of 10Gy in one fraction. 21 Ogawa et al from Tokyo, Japan, have published their experience with different fractionation schedules through the years ranging from 20Gy in four fractions to 8 Gy in single fraction.…”
Section: Discussionmentioning
confidence: 99%